2015
DOI: 10.1037/emo0000059
|View full text |Cite
|
Sign up to set email alerts
|

Emotional inertia and external events: The roles of exposure, reactivity, and recovery.

Abstract: Increased moment-to-moment predictability, or inertia, of negative affect has been identified as an important dynamic marker of psychological maladjustment, and increased vulnerability to depression in particular. However, little is known about the processes underlying emotional inertia. The current article examines how the emotional context, and people's responses to it, are related to emotional inertia. We investigated how individual differences in the inertia of negative affect (NA) are related to individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
115
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 66 publications
4
115
1
Order By: Relevance
“…Deviations from this baseline that are too great trigger a “pull back” reaction to maintain the default organization. Consistent with this idea, negative emotion inertia predicts less negative emotion recovery after exposure to negative stimuli, which the authors hypothesize to be an impairment in mood repair (Koval et al, in press). …”
Section: A Dynamic Systems Framework For Understanding Depression Andmentioning
confidence: 90%
See 1 more Smart Citation
“…Deviations from this baseline that are too great trigger a “pull back” reaction to maintain the default organization. Consistent with this idea, negative emotion inertia predicts less negative emotion recovery after exposure to negative stimuli, which the authors hypothesize to be an impairment in mood repair (Koval et al, in press). …”
Section: A Dynamic Systems Framework For Understanding Depression Andmentioning
confidence: 90%
“…Koval et al, in press; Thompson et al, 2012). Wichers and colleagues (2011) illustrate this method in the context of providing person-tailored feedback in everyday life.…”
Section: New Methods and Technological Advancements For The Study Of mentioning
confidence: 99%
“…Due to conditional branching in the presentation of items during the Ambulatory Assessment, participants answer 31 to 50 items (Additional file 2: Tables S1, S2 and S3) at each signal six times per day regarding (1) positive and negative affect [48, 49], (2) worrying [24, 50], (3) momentary emotion regulation strategies [12], (4) attention (item from previous research in our laboratory) and (5) situational circumstances (items from several Ambulatory Assessment prompts [8, 11, 12, 51]). If a participant indicates a specific desire, additional items appear on the smartphone screen depending on the indicated desire: for example, if a given participant indicates the desire “food”, items are presented that assess specific eating behaviors.…”
Section: Methodsmentioning
confidence: 99%
“…Ambulatory Assessment allows for tapping into the momentary experiences and the situational context that impact the enactment of self-control in a given real-life situation. Due to these advantages, Ambulatory Assessment strategies have been used to study self-control in a broad range of health-related domains, such as smoking [11], emotion regulation [12] or eating behavior [13] and have led to the identification of a range of predictors in these fields.…”
Section: Introductionmentioning
confidence: 99%
“…High levels in affective inertia can be interpreted as regulatory weakness (De Haan-Rietdijk et al 2016), with a reduced ability to disengage from recent events resulting in previous experiences spilling over into the future (Suls et al 1998). Evidence for this assumption has been provided by Koval et al (2015), who found increased negative affect inertia to be associated with less negative affect recovery from negative stimuli in both a laboratory and a real-life setting.…”
mentioning
confidence: 99%